Transitividade verbal e planos discursivos : um estudo funcionalista da hipotaxe adverbial causal em elocuções formais - Nascimento, Simone Maria Barbosa Nery (2009)
The aim of this paper is to analyze transitivity and discourse plans on the combination of causal hypotactic clauses and the main clauses related to them.The research is based on Hopper & Thompson1s (1980) Transitivity in grammar and discourse, taxonomy of 10 syntactic-semantic parameters which grade transitivity and help identifying foregrounding and backgrounding in discourse. These 10 parameters will be tested on causal hypotactic clauses and on the main clauses with which they combine. The aim of this test is to verify the validity of the hypothesis that causal hypotactic clauses function as background for the main clauses with which they combine. The research corpus is formed by 10 formal elocutions (lectures and oral presentations) which belong to Funcpar (Functional Research Group on North/ North-East of Paraná) database. The subjects of the research are lecturers and university students who were born in Maringá (PR) or have lived in it for at least 10 years. The data were recorded during graduation classes and oral presentations and were transcribed according to a pattern based on NURC project (PRETI, 1993, p.11-12) with a few adaptations. The segmentation of the units of the corpus followed Chafe's (1987) concept of intonation units. Results of the research have confirmed the initial hypothesis that causal hypotactic clauses analyzed under the view of transitivity parameters function as background for the main clauses with which they combine. It was found that these causal hypotactic clauses are usually in a late position in the clause and add new information in order to enhance the main clause. It was also possible to point that the speakers' most used was because. When causal clauses function as background, they hold a relation at content level. When they function as foreground (despite the very low frequency), they hold a relation at speech act level, which is syntactically looser. Therefore, it is possible to conclude that pragmatic factors have influence over the organization of causal hypotactic clause combining.